2020
DOI: 10.1002/path.5574
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐200c‐3p promotes endothelial to mesenchymal transition and neointimal hyperplasia in artery bypass grafts

Abstract: Increasing evidence has suggested a critical role for endothelial‐to‐mesenchymal transition (EndoMT) in a variety of pathological conditions. MicroRNA‐200c‐3p (miR‐200c‐3p) has been implicated in epithelial‐to‐mesenchymal transition. However, the functional role of miR‐200c‐3p in EndoMT and neointimal hyperplasia in artery bypass grafts remains largely unknown. Here we demonstrated a critical role for miR‐200c‐3p in EndoMT. Proteomics and luciferase activity assays revealed that fermitin family member 2 (FERM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 95 publications
2
27
0
Order By: Relevance
“…WT and neutrophil elastase_KO VSMCs (0.75 × 10 4 per well) were cultured in 96‐well plates overnight, followed by serum starvation for 48 h. Starved VSMCs were incubated with 10‐μM H 2 O 2 for additional 24 h to induce apoptosis. Cell viability was evaluated using Cell Counting Kit‐8 (Sigma/Merck, 96992‐500TESTS‐F) according to the manufacturer's instructions as described previously (Chen et al, 2021). The absorbance of the samples was measured by a microplate reader at 450 nm (OD 450 ), and relative absorbance ( A 450 nm ) values representing cell viability were compared between treatments with control sample set as 1.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WT and neutrophil elastase_KO VSMCs (0.75 × 10 4 per well) were cultured in 96‐well plates overnight, followed by serum starvation for 48 h. Starved VSMCs were incubated with 10‐μM H 2 O 2 for additional 24 h to induce apoptosis. Cell viability was evaluated using Cell Counting Kit‐8 (Sigma/Merck, 96992‐500TESTS‐F) according to the manufacturer's instructions as described previously (Chen et al, 2021). The absorbance of the samples was measured by a microplate reader at 450 nm (OD 450 ), and relative absorbance ( A 450 nm ) values representing cell viability were compared between treatments with control sample set as 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…Proteomic studies and data analysis were conducted as described in our previous studies (Afzal et al, 2016; Chen et al, 2021; Xiao et al, 2014). Briefly, serum‐starved neutrophil elastase_KO VSMCs treated with vehicle or 100‐ng·ml −1 active human neutrophil elastase (ab91099) were directly lysed in a urea‐based lysis buffer, and proteins were digested using trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, miR-200b overexpression also induces the down-regulation of p300, a transcription coactivator known to contribute to cardiac fibrosis and hypertrophy via TGF-β/SMAD ( Bugyei-Twum et al, 2014 ; Feng et al, 2016 ). Although the inhibitory role of the whole miR-200 family is well established, both in EMT ( Korpal and Kang, 2008 ; Korpal et al, 2008 ) and EndMT ( Feng et al, 2016 ; Zhang et al, 2017 ), unexpectedly a recent study shown that miR-200c-3p exerted the opposite effect, being able to promote EndMT and aortic graft remodeling both in vivo and in vitro ( Chen et al, 2021 ). Finally, a further TGF-β/SMAD pathway-mediated regulatory mechanism involves miR-451 whose effects on EndMT are AMPK-dependent.…”
Section: Mirnas Regulation Of Dcm-associated Endmtmentioning
confidence: 99%
“…For example, the EndMT process that relies on miR-200 family is a reasonable biological mechanism that makes the bicuspid aortic valve more prone to aneurysms [22]. A previous study has confirmed that miR-200c-3p is highly expressed in human femoral arteries with atherosclerotic lesions [23]. The miR-200c-3p expression is also increased in the NaF-treated HUVECs, and NaF promotes apoptosis of HUVECs by regulating miR-200c-3p/Fas pathway [24].…”
Section: Discussionmentioning
confidence: 97%